PENGEMBANGAN LKPD BERBASIS MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Esti Nurlatifah; Sugeng Riyadi; Awatif (Pendidikan Matematika | STKIP YM Bangko, 2022)
One of the problems that occur in the world of education is the lack of teaching materials that can help students understand subject matter focusing on concepts. The method that can be used is mind mapping. Mind mapping can make students develop mathematical creative thinking skills. This study aims to produce mind mapping based LKPD teaching materials for mathematical creative thinking skills. Using the Research and Development development method with the 4-D model. This mind mapping based LKPD was validated by 5 validators with a validity score of 4.47 which was categorized as very valid. practicality is obtained from the results of a questionnaire with a score of 92.25%. Based on the results of the study, it was found that the LKPD based on mind mapping on the ability to think creative mathematically on the material of equations and linear inequalities of one variable developed was very valid and very practical